The Influence of Prices and Promotions on Purchasing Decisions on Dine-in Services at McDonald’s Cideng, Central Jakarta - Putranto, Ivan; Syamruddin, Syamruddin; Eliyani, Citra (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
The purpose of this research is to determine the effect of prices and promotions on customers' purchasing decisions for dine-in services at McDonald’s Cideng, Central Jakarta, both partially and simultaneously. The method used in this research is associative quantitative with a population of 37,500 customers taken as a sample of 100 respondents. The sampling technique uses a probability sampling method, namely accidental sampling. The data analysis techniques in this research are: simple linear regression analysis, multiple linear regression analysis, and coefficient of determination analysis. Then hypothesis testing is the t test and f test. The results of this research are that price influences purchasing decisions, this can be seen from the t test with the calculated t value > t table or (10.084 > 1.660). This is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0, 05). Promotions influence purchasing decisions this can be seen from the t test with the calculated t value > t table or (9.126 > 1.660). This is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0.05). Price and promotions influence purchasing decisions, this can be seen from the results of the f test where F calculated > F table or (73.628 > 2.70), this is also reinforced by ρ value < Sig.0.05 or (0.000 < 0, 05).